FACTORS ASSOCIATED WITH ASTHMA IN BRAZILIAN ADOLESCENTS: NATIONAL ADOLESCENT SCHOOL-BASED HEALTH SURVEY (PENSE-2012) - Bianca Caroline Elias; Janiquelli Barbosa Silva; Laís Amaral Mais; Sarah Warkentin; Tulio Konstantyner; Dirceu Solé
ABSTRACT Objective: To identify factors associated with asthma in Brazilian adolescents. Methods: Cross-sectional study based on data from the 2012 National Adolescent School-based Health Survey (PeNSE), a Brazilian survey applied by a self-reported questionnaire in a representative sample of 9th-grade students. Descriptive and inferential analysis was made based on the demographic, socioeconomic, clinical, food consumption and environmental characteristics potentially associated with asthma. Adolescents who presented wheezing in the last 12 months were considered asthmatic. A multiple logistic regression model was adjusted for confounding factors. Significance was defined as p≤0.05. Results: A total of 106,983 adolescents were studied. The prevalence of asthma was 23.2%. The final model was composed of 11 variables that were independently associated with asthma: female sex (OR=1.17), <14 years old (OR=1.12), not living with parents (OR=1.06), the highest number of days consuming ultra-processed foods (OR=1.16), lunch or dinner time without presence of parents or guardians (OR=1.13), meals in front of the TV or while studying (OR=1.18), not having breakfast frequently (OR=1.22), having smoked cigarettes (OR=1.36), having tried alcoholic beverage (OR=1.37), having used illicit drugs (OR=1.29) and having sought health care in the last year (OR=1.67). Conclusions: The results of the present study reinforce the multifactorial characteristic of asthma diagnosis. Prevention and control strategies should focus on groups of adolescents living in inadequate conditions when it comes to family dynamics, food consumption and behavior (drug use).